Sodium Butyrate Protects N2a Cells against Aβ Toxicity In Vitro - Jingxuan Sun; Boyu Yuan; Yancheng Wu; Yuhong Gong; Wenjin Guo; Shoupeng Fu; Yongxin Luan; Wei Wang (Mediators of Inflammation)
Alzheimer’s disease (AD) is a common neurodegenerative disease. Aβ plays an important role in the pathogenesis of AD. Sodium butyrate (NaB) is a short-chain fatty acid salt that exerts neuroprotective effects such as anti-inflammatory, antioxidant, antiapoptotic, and cognitive improvement in central nervous system diseases. The aim of this study is to research the protective effects of NaB on neurons against Aβ toxicity and to uncover the underlying mechanisms. The results showed that 2 mM NaB had a significant improvement effect on Aβ-induced N2a cell injury, by increasing cell viability and reducing ROS to reduce injury. In addition, by acting on the GPR109A receptor, NaB regulates the expression of AD-related genes such as APP, NEP, and BDNF. Therefore, NaB protects N2a cells from Aβ-induced cell damage through activating GPR109A, which provides an innovative idea for the treatment of AD.